Dependence of charge separation efficiency on film microstructure in Poly(3-hexylthiophene-2,5-diyl): [6,6]-phenyl-C61 butyric acid methyl ester blend films - Keivanidis, Panagiotis E.; Clarke, Tracey M.; Lilliu, Samuele; Agostinelli, Tiziano; MacDonald, J. Emyr; Durrant, James R.; Bradley, Donal D.C.; Nelson, Jenny (My University, 2010)
Herein we address the factors controlling photocurrent generation in P3HT:PCBM blend films as a function of blend composition and annealing treatment. Absorption, photoluminescence, and transient absorption spectroscopy are used to distinguish the role of exciton dissociation, charge pair separation, and charge collection. Variations in blend film microstructure with composition and annealing treatment are studied using X-ray diffraction. While the trend in photocurrent generation with composition and annealing [Muller, et al., Adv. Mater. 2008, 20, 3510] does not follow the trend in exciton dissociation, it closely follows the trend in charge pair generation. Moreover, charge pair generation efficiency is positively correlated to the degree of polymer crystallization and the appearance of large domains of both polymer and fullerene phases. We argue that larger domains assist charge pair separation by increasing the probability of escape from the P3HT:PCBM interface, thus reducing geminate charge recombination. © 2010 American Chemical Society.
Keywords: Kinetics; Spectroscopy